An inquiry into the foreign systems of registering dealings with land by means of maps and indexes - Mayne, Edward Graves (Statistical and Social Inquiry Society of Ireland, 1852)
In pursuance of your reference to me, to inquire into "The system of registration of dealings with land, adopted in the United States of America, and on the Continent of Europe, with a view to ascertain the most convenient plan for constructing a land index founded on a public map, as the basis of a General Register;" I beg to submit to you the following report.
Keywords: Land registration; Maps; 314.15